Electrochemical properties of Electric Arc Furnace Slag for degradation of Acid Orange II / Iman Athirah Khamis and Dr. Norhaslinda Nasuha - Khamis, Iman Athirah; Nasuha, Norhaslinda (2020)
Electrochemical properties of Electric Arc Furnace Slag (EAFS) derived from metal steel waste as potential electrode for degradation of Acid Orange II (model pollutant). The objectives of this research are to study the oxidation and reduction process of EAFS through electro-Fenton reaction process using cyclic voltammetry (CV) and to analyze the potential of EAFS for degradation of Acid Orange II (AO2) through cyclic voltammetry profile. This research project is conduct to analyze two types of electrode which were IO electrode and EAFS electrode using CV. The scan rate for each sample were varies (10, 20, 30, 40, 50, and 60 mV/s). From results obtained, effect of various scan rate on IO and EAFS electrode is observed for the CV pattern. EAFS electrode show great rate capability along with efficient pseudocapacitive performance. The occurrence of oxidation and slight reduction occur in EAFS electrode prove the potential of the electrode based on the CV pattern.